Sequence Manipulation with Orthography Profiles in JavaScript (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2023)
Orthography profiles allow for the explicit simultaneous segmentation and conversion of sequences from one orthography to another. They play a crucial role in the standardization workflows developed as part of the Cross-Linguistic Data Formats initiative, where they are used to convert original orthographies used for language documentation to a strict version of the International Phonetic Alphabet. Given that the basic algorithm by which orthography profiles can be used to segment and convert sequences across orthographies is very straightforward, it can be easily implemented in JavaScript.
Keywords: orthography profile; JavaScript